Transcriptome analysis of "Candidatus Liberibacter solanacearum" in its psyllid vector, Bactericera cockerelli. - Freddy Ibanez (Public Library of Science (PLoS), 2014)
"Candidatus Liberibacter solanacearum" (Lso) is an emergent pathogen of carrots in Europe and solanaceous plants in North and Central America and New Zealand. This bacterium is closely related to other pathogenic Candidatus Liberibacter spp., all vectored by psyllids. In order to understand the molecular interaction of this pathogen and its psyllid vector, Bactericera cockerelli, Illumina sequencing of psyllid harboring Lso was performed to determine if this approach could be used to assess the bacterial transcriptome in this association. Prior to sequencing, psyllid RNA was purified and insect and bacterial rRNA were removed. Mapping of reads to Lso genome revealed that over 92% of the bacterial genes were expressed in the vector, and that the COG categories Translation and Post-translational modification, protein turnover, chaperone functions were the most expressed functional categories. Expression levels of selected Lso genes were confirmed by RT-qPCR. The transcriptomic analysis also helped correct Lso genome annotation by identifying the expression of genes that were not predicted in the genome sequencing effort.